Modern physics - Krane, Kenneth S. (Wiley (India), 2012)
"This is a much awaited revision of a modern classic that covers all the major topics in modern physics, including relativity, quantum physics, and their applications. Krane provides a balanced presentation of both the historical development of all major modern physics concepts and the experimental evidence supporting the theory"--